Effect of active versus passive recovery on performance during intrameet swimming competition - Hinzpeter, J.; Zamorano, A.; Cuzmar, D.; Lopez, M.; Burboa, J. (Sports Health: A Multidisciplinary Approach, 2014)
During competition, high-performance swimmers are subject to repeated physical demands that affect their final performance. Measurement of lactate concentration in blood seeks to indirectly gauge physiologic responses to the increase in physical exercise. Swimmers face multiple maximal-exertion events during competition. Strenuous physical exercise leads to fatigue and, thus, a decrease in sports performance.